Confronting Occupation with Cultural Stability in Lameece and Jacob’s Food and Fadwa - Mokbel, Sahar (European Scientific Journal, ESJ, 2018)
The following paper demonstrates the life in Palestine and the daily conflicts that take place due to Israeli occupation of the land. Its purpose is to shed the light on the significance of confronting occupation with cultural stability. Through the play Food and Fadwa, we are introduced to a Palestinian family suffering from the ache of occupation. However, Fadwa’s Palestinian cuisines act as means of resistance against the Israeli attempts of cleansing the Palestinian culture and heritage.